If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -3a = 8 + -2(2a + 7) Reorder the terms: 2 + -3a = 8 + -2(7 + 2a) 2 + -3a = 8 + (7 * -2 + 2a * -2) 2 + -3a = 8 + (-14 + -4a) Combine like terms: 8 + -14 = -6 2 + -3a = -6 + -4a Solving 2 + -3a = -6 + -4a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '4a' to each side of the equation. 2 + -3a + 4a = -6 + -4a + 4a Combine like terms: -3a + 4a = 1a 2 + 1a = -6 + -4a + 4a Combine like terms: -4a + 4a = 0 2 + 1a = -6 + 0 2 + 1a = -6 Add '-2' to each side of the equation. 2 + -2 + 1a = -6 + -2 Combine like terms: 2 + -2 = 0 0 + 1a = -6 + -2 1a = -6 + -2 Combine like terms: -6 + -2 = -8 1a = -8 Divide each side by '1'. a = -8 Simplifying a = -8
| 2x+3+(2y-2)yi=0 | | 20=2w+4 | | 5.2(x-2.25)=-20.4 | | 18=2h-4 | | 54=-9a | | 4z+2=6z | | 12x^2+2x=5 | | 3(4-c)=-4(c-6) | | -8=a/-10 | | 4.375=7/8(b-4) | | -8=s/-10 | | (2a+9)(5a-6)=0 | | -5-4(6+7y)= | | 4x-(-2)-7x+12=5 | | -6x+21.4=2.2 | | 5n=3n+27 | | 100=p/10 | | -(4y+3)-(-3y-7)=1 | | (8h-1)(2h-3)=0 | | 3w+3=5w+7 | | 103.5=9(m+3.7) | | (4n+3)(n+9)=0 | | b+b+b+22=b+b+6 | | 4x+4=-7+2x+25 | | -7(-2-6b)+9b= | | 12p+3=30 | | pie=7.3m | | 2u-10=0 | | 2w+3.7=0.5 | | 13x-34=10x-10 | | (b-7)(b+3)=0 | | 2u-10=14 |